Model-based predictive controller for real-time industrial applications - Ling, Keck Voon. (2008)
This report gives the formulation of the state space Generalised Predictive Control as published in (Ling and Lim, 1996). Both the single rate and multirate control schemes are presented. It then presents a detail analysis of the state estimation scheme.